2019
DOI: 10.1002/jtr.2282
|View full text |Cite
|
Sign up to set email alerts
|

Tourists' reflections on sustainability in a biosphere reserve landscape

Abstract: There is a lack of critical engagement and a focus on practical solutions in sustainable tourism debates. Research on biosphere reserve (BR) tourists has focused mainly on descriptions, while not critically engaging in issues relating to sustainable tourism.This article explores tourists' reflections on sustainable development in the landscape of a Swedish BR. The findings indicate that BR landscapes can increase environmental awareness, that aesthetics are important to how tourists make sense of sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…However, adventure businesses' opinions about the importance that customers attach to sustainability is striking, showing that customers do not choose them for sustainability. This reinforces Hoppstadius's (2019) finding that tourism in biosphere reserves is not more sustainable than other types of tourism.…”
Section: External Driverssupporting
confidence: 84%
See 1 more Smart Citation
“…However, adventure businesses' opinions about the importance that customers attach to sustainability is striking, showing that customers do not choose them for sustainability. This reinforces Hoppstadius's (2019) finding that tourism in biosphere reserves is not more sustainable than other types of tourism.…”
Section: External Driverssupporting
confidence: 84%
“…Furthermore, adventure travel offers a practical sense of sustainable development. Different authors show how nature, landscape, and tourism entrepreneurs' environmental consciousness can influence tourists in different Cuadernos de Turismo, 50, (2022), 1-20 ways (Hoppstadius, 2019;UNWTO, 2014). The transformative experiences of adventure travel are a way to help clients understand how their immediate and sometimes ongoing support can help preserve a destination's key cultural and natural capital (UNWTO, 2014).…”
Section: Adventure Tourismmentioning
confidence: 99%
“…Tourism provides a context to decrease the gap between climate change information and behaviour intention. It has been widely discussed that participating in tourism activities might increase people's environmental awareness (e.g., Hoppstadius, ; Horng, Hu, Teng, & Lin, ). This is particularly true for ski tourism, where tourist's experience is highly sensitive to climate.…”
Section: Introductionmentioning
confidence: 99%
“…Kratzer (2018a) conducted a bibliometric analysis of biosphere reserve research between 1977 and 2016 and found tourism (as part of the economic discipline) to be far less investigated than other topics or disciplines like biodiversity and climate change. Recent sustainable tourism studies in biosphere reserves include revitalising ecotourism (Habibah et al, 2013); sustainable development and ecotourism (Hoppstadius & Dahlström, 2015); the relationship between tourism and the biosphere reserve status (Barukchieva, 2017); tourism entrepreneurs' learning through interactions with tourists (Hoppstadius & Möller, 2018); segmenting tourists (Gu et al, 2018); types of tourism development approaches that are sustainable (Hoppstadius & Sandell, 2018); tourists' reflections on sustainability (Hoppstadius, 2019); community involvement and tourism revenue sharing as contributors to the SDGs (Carius & Job, 2019); ecotourism as a learning tool for sustainable development (Mondino & Beery, 2019); evaluating tourist nature-based experiences (Moreno-Llorca et al, 2020); and tourism as a means to livelihood diversification (Bires & Raj, 2020). In most of this research, the case studies were conducted in well-established biosphere reserves that have a long history of tourism practices.…”
Section: Biosphere Reserves and Sustainable Tourism Researchmentioning
confidence: 99%